Association between nutritional factors and myopia in adolescents: a systematic review and meta-analysis - Xu, Zhaoxia (Frontiers in Public Health, 2025)
BackgroundMyopia is a highly prevalent eye disorder among adolescents, and an increasing body of research indicates that nutritional factors may have a significant impact on its development. However, the nature and extent of these relationships remain unclear. This systematic review and meta-analysis aimed to comprehensively evaluate the associations between various nutritional factors, including carbohydrates, proteins, cholesterol, and sodium, and myopia in adolescents.MethodsMultiple databases, such as PubMed, Web of Science, Scopus, and Embase, were systematically searched up to February 15, 2025. The inclusion criteria encompassed observational studies published in English, involving adolescents (aged 6–18 years), and reporting data on the intake of the selected nutritional factors and myopia status. Two reviewers independently screened studies, extracted data, and assessed study quality using the Newcastle-Ottawa Scale. Standardized mean differences (SMDs) with 95% confidence intervals (CIs) were calculated for continuous outcomes. Random-effects models were applied to account for potential heterogeneity.ResultsA total of 7 articles (8 studies) involving 45,993 adolescents were included. Pooled analysis revealed significant associations between nutritional factors and myopia risk. Higher carbohydrate intake was positively linked to myopia (SMD = 0.36, 95% CI: 0.22–0.50, I2 = 94.8%, p < 0.001), while protein intake showed a protective effect (SMD = −0.25, 95% CI: −0.27 to −0.23, I2 = 44.0%, p < 0.001). Cholesterol intake was associated with increased myopia risk (SMD = 0.20, 95% CI: 0.10–0.31, I2 = 91.7%, p < 0.001), and sodium intake demonstrated a strong positive association (SMD = 1.07, 95% CI: 0.93–1.22, I2 = 96.0%, p < 0.001). Sensitivity analyses confirmed the robustness of results, and no publication bias was detected.ConclusionThis study suggests potential associations between nutritional factors and myopia in adolescents. Carbohydrates, cholesterol, and sodium were positively associated with myopia, whereas proteins showed a possible protective effect. However, given the small number of available studies, the predominance of cross-sectional designs, and substantial heterogeneity, these findings should be considered preliminary. Future well-designed, longitudinal or interventional studies are required to confirm these associations before any firm dietary recommendations can be made for myopia prevention.